Systems of Geo Positioning of the Mobile Robot; IOP Conference Series: Materials Science and Engineering; Vol. 221 : Innovative Technologies in Engineering - Momot M. V. Mikhail Viktorovich; Proskokov A. V. Andrey Vladimirovich; Nesteruk D. N. Dmitry Nikolaevich; Ganiyev M.; Biktimirov A. S. (2017, 2017)
Title screen